2017
DOI: 10.1038/pr.2017.3
|View full text |Cite
|
Sign up to set email alerts
|

The association between weight, height, and head circumference reconsidered

Abstract: Under appropriate nutritional and health circumstances, nutritional status, body size, and head circumference are not related.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
11
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 12 publications
(5 reference statements)
2
11
0
3
Order By: Relevance
“…Studies of body growth and brain development suggest that brain size is not determined by body size (27). Furthermore, a recent study of 14,819 children under 7 years of age found that after the age of 2 head growth seemed to progress independently of skeletal growth and body size (28). Therefore, different mechanisms may underlie the observed restricted brain and body development.…”
Section: Discussionmentioning
confidence: 99%
“…Studies of body growth and brain development suggest that brain size is not determined by body size (27). Furthermore, a recent study of 14,819 children under 7 years of age found that after the age of 2 head growth seemed to progress independently of skeletal growth and body size (28). Therefore, different mechanisms may underlie the observed restricted brain and body development.…”
Section: Discussionmentioning
confidence: 99%
“…We believe that the replication results imply important clues towards true associations. Second, the unbalanced sample sizes used in the MTAG analysis may elevate false positive rate, as described by the MTAG authors (Scheffler et al, 2017). We tackled this issue by monitoring both the original and the integrative association signals for any unusual difference (e.g., non- to extreme significance).…”
Section: Discussionmentioning
confidence: 99%
“…Many studies attempt to define some conceptual growth parameters by integrating the three traits to comprehensively reflect children’s health status (Sankilampi et al, 2013; Haksari et al, 2016). Their high phenotypic correlation (Scheffler et al, 2017) implies that these traits may share some common genetic architecture.…”
Section: Introductionmentioning
confidence: 99%
“…The observation that final HC is largely determined by the age of 6 years in a large study from the UK 7 is therefore likely to be valid in multiple populations. In addition, nutritional status, body size, and HC are closely correlated for healthy children during early life, and become less related after 24 months of age 8 . While HC properties in early childhood have immediate medical relevance, there are also compelling reasons to study HC in adulthood.…”
Section: Introductionmentioning
confidence: 99%